2007
DOI: 10.1136/ip.2006.014662
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception, road behavior, and pedestrian injury among adolescent students in Kathmandu, Nepal

Abstract: Objective:To examine the relationship between the perceived safety of specified road behaviors, self-described road behaviors, and pedestrian injury among adolescent students in Kathmandu, Nepal.Methods:A cross-sectional study was conducted among 1557 adolescents in grades 6–8 across 14 schools in Kathmandu using a self-administered questionnaire in 2003. A multiple logistic regression analysis was used to analyze the data.Results:Adolescents were more likely to suffer from pedestrian injury when they did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 24 publications
1
48
1
Order By: Relevance
“…Howe et al (2006) identified that mental health status of caregivers is highly associated with all types of injuries in young children (infants and toddlers); while Mashreky et al (2009) reported that the relative risk of burn injuries is seven times higher in children under five years compared with children over five years and adults. Regarding the risk of pedestrian injuries, Poudel-Tandukar et al (2007) reported that children from poor households (no television ownership) have higher risk of injuries, however, other factors, such as distance to school, number of road crossings on the school journey and road use behaviours did not show statistical significance. Rahman et al (2006) analysed the risk factors for childhood drowning, which found that mothers aged over 30 years, illiterate mothers and lower family income were significantly associated with drownings.…”
Section: Injury Risk Factors Identified By the Authorsmentioning
confidence: 91%
See 1 more Smart Citation
“…Howe et al (2006) identified that mental health status of caregivers is highly associated with all types of injuries in young children (infants and toddlers); while Mashreky et al (2009) reported that the relative risk of burn injuries is seven times higher in children under five years compared with children over five years and adults. Regarding the risk of pedestrian injuries, Poudel-Tandukar et al (2007) reported that children from poor households (no television ownership) have higher risk of injuries, however, other factors, such as distance to school, number of road crossings on the school journey and road use behaviours did not show statistical significance. Rahman et al (2006) analysed the risk factors for childhood drowning, which found that mothers aged over 30 years, illiterate mothers and lower family income were significantly associated with drownings.…”
Section: Injury Risk Factors Identified By the Authorsmentioning
confidence: 91%
“…Only seven papers reported the statistical analysis of risk factors (Chowdhury et al, 2009;Dandona et al, 2008;Howe et al, 2006;Mashreky et al, 2009;Poudel-Tandukar et al, 2007;Rahman et al, 2006;Rathinam et al, 2007). Age, gender and place of residence were the most widely reported risk factors for all injuries combined.…”
Section: Injury Risk Factors Identified By the Authorsmentioning
confidence: 98%
“…Younger drivers that are more likely to have risky behaviors lead to a greater fatality risk when they are involved in crashes [19,25,26]. Male pedestrians who usually have more risky behaviors than females are more likely to be severely injured [21,[27][28][29]. Drivers and pedestrians under the influence of alcohol behave riskily, which in turn increases the probability of injury severity [14,[18][19][20][21][22]25,26].…”
Section: Introductionmentioning
confidence: 99%
“…This has been the major focus of a number of pedestrian studies. For example, studies dealing with pedestrian safety, in both signalised and un-signalised intersections, have been carried out by Muraleetharan et al [21], King et al [3] and Guo et al [22]; pedestrian risk-taking behaviour [4,23,24], such as drunk pedestrians [25], distracted walking [26], illegal pedestrian crossing behaviour [3,26], across different age groups, such as child pedestrians [27] and college students [26]; modelling pedestrian behaviour [28]; and pedestrian safety factors [5]. However, traffic signals are effective only when traffic rules are enforced as intended.…”
Section: Walkability and The Evaluation Of Pedestrian Crossings: A Rementioning
confidence: 99%